347 The evaluation of feed acidification with feed grade sodium formate on wean to finish pig performance. (10th April 2018) - Graham, A; Jendza, J A; Chen, H Y
Abstract: In study one, 1, 200 pigs (PIC 337 × Camborough; PIC, Hendersonville, TN) started at 5.91 kg were allocated to one of 4 dietary feed grade sodium formate regimens (Amasil NA, BASF, Florham Park, NJ) to evaluate the inclusion of sodium formate on wean-finish pig performance. Dietary treatments consisted of: 1. Basal diet, 2. 3 g Amasil/kg from wean to finish, 3. 6 g Amasil/kg from wean to the end of the grower period (d 84) and again at 106.6 kg BW, and 4. 9 g Amasil/kg from wean to the end of the nursery period (d 42) and again at 106.6 kg BW. A second study, evaluated 0, 3, 6, and 9 g Amasil NA/kg during the grow-finish (30-74 kg BW) period using an additional 48 single gender pens. Pigs were blocked by sex and equalized weight. The diets fed in both studies were all in meal form and were formulated to meet or exceed current NRC (2012) recommendations. Mortalities and pen removals were weighed and recorded. Pigs were PRRS and PEDV negative and were vaccinated for PCV2, Mycoplasma hyopneumoniae, Salmonella and Lawsonia. Data were analyzed as a randomized complete block design using Proc mixed with pen as the experimental unit, treatment as the fixed effect, and block as the random effect. In study 1, there were significant reductions in ADG and improvements in G:F with the inclusion of sodium formate in weeks 2-3 (0.88, 0.83, 0.83, 0.84 ± 0.01 kg/d; P =0.02; and 0.68, 0.75, 0.74, 0.78 ± 0.04; P =0.01, respectively). Furthermore, there was a significant improvement (0.41, 0.42, 0.42, 0.42 ± 0.02, respectively; P =0.03) in G:F from d0 through the first market with the use of the sodium formate with no differences in ADG. In study 2, there was a tendency for improvement in ADG (0.94, 0.97, 0.95, 0.96 ± 0.02 kg/d, respectively; P =0.09) when pigs were fed 3g of Amasil/ kg of feed from the start of the study for the 42 days. In conclusion, the use of feed grade sodium formate improves feed efficiency in the nursery and that may be carried over into the grow-finish period.